Association of IGF-1 and IGFBP-3 with metabolic abnormalities among children and adolescents - Zhao, Zhenghao; Ma, Yuanyuan; Zhang, Xinyi; Liu, Xiaoxiao; Li, Yang; Fang, Zhongze; Zheng, Rongxiu; Li, Jing (Frontiers in Endocrinology, 2025)
Background and ObjectiveInsulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) play roles in growth and development, but their association with metabolic abnormalities in children and adolescents remains unclear. This study aimed to investigate the relationship between IGF-1, IGFBP-3, and metabolic abnormalities in Chinese children and adolescents, while assessing the role of age in these associations.MethodsParticipants were categorized into low-risk and high-risk groups based on metabolic abnormality criteria. Demographic, anthropometric, and laboratory data were collected via medical records. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs).ResultsData from 588 participants were analyzed. Higher IGF-1 (Q4: OR 0.24, 95% CI: 0.11–0.51) and IGFBP-3 levels (Q4: OR 0.38, 95% CI: 0.18–0.76) were associated with lower odds of metabolic abnormalities. Higher IGF-1/IGFBP-3 ratios also reduced metabolic abnormality risk. Age-related trends showed IGF-1 levels plateaued with age, while IGFBP-3 progressively increased, with the low-risk group consistently maintaining higher levels.ConclusionsHigher IGF-1 and IGFBP-3 levels are negatively associated with metabolic abnormalities in children and adolescents. Maintaining the balance of these factors is critical for metabolic health, especially during adolescence.